Design and Implementation of HINSPELL -Hindi Spell Checker using Hybrid approach (International Journal of Scientific Research and Management (IJSRM), 2015)
A spell checker is an application program that flags words in a document that may not be spelled correctly. A spell checker is a basic need of a word processor of any language. Spell checker analyzes the written text in order to identify any misspellings and gives best correct suggestions for those misspellings. Most of work has been done in English and Punjabi language. Hindi is the third most spoken language in the world. In This paper the design, techniques and implementation of the Hindi spell checker is proposed. Error detection, Error correction by generating suggestions and replacement are the main features of this system. The system detects approximately 83.2% of the errors and provides 77.9% of the correct suggestions for the misspelled words.